The effect of metal EOS 316L stainless steel additive manufacturing powder recycling on part characteristics and powder reusability. Issue 2 (3rd April 2019) - Quinn, P.; O'Halloran, S.; Lawlor, J.; Raghavendra, R.
ABSTRACT: Direct metal laser sintering (DMLS) is a powder bed fusion (PBF) process commonly used within the medical device and aerospace industries to fabricate high value, complex components. Powder material used in the DMLS process can be costly and it is rare for a single build to require a full batch of powder. The un-melted powder, which differs in particle size and morphology from virgin powder, is often recycled for further builds. This work presents a study of the effects that recycling a stainless steel metal powder used in the DMLS process has on finished parts. Hence, in this paper, powder material characteristics, such as particle size, particle morphology and bulk chemical composition have been monitored throughout the recycling process. An analysis of parts manufactured via DMLS on an EOS M280 demonstrate the negative effect of powder recycling on part quality in terms of surface roughness, part density, hardness and dimensional accuracy. Results from this research provide an insight to the effect that recycling AM powders has on the powder characteristics and on the quality of the parts produced.